Application of Pension Fund and Jubilee (Case Study of PG Rejo Agung Baru Madiun) - Iwan Suhasto; Shinta Anggraeny; Dewi Kirowati (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2022)
PG Rejo Agung Baru Madiun is a sugar factory managed by PT PG Rajawali I, a subsidiary of state-owned agribusiness PT Rajawali Nusantara Indonesia (RNI). PG Rejo Agung Baru has several sections, one of which is HR and General Affairs. The HR and General Affairs department handles matters relating to employees which include employee salaries, employee pension funds, jubilees, promotions, employee recruitment and so on. Companies need information relating to employees quickly and accurately to make a decision. Decision making is something that is very vital in the company. This study aims to design and build a web-based application for calculating pension and jubilee funds. This application for calculating pension and jubilee funds was created to solve the problems faced by the HR and General Department, namely the manual processing of employee data. The pension and jubilee fund application can increase the efficiency of the pension and jubilee calculation because the admin does not need to do the calculations manually, besides that this application can also help reduce the risk of human error in the process of calculating age, salary, severance pay, pension benefits, taxes and jubilee. The report generated from this application has a consistent format so as to support the process of managing pension funds and jubilee consistently